A systematic review of early speech interventions for children with cleft palate. Issue 1 (12th November 2021) - Lane, Hannah; Harding, Sam; Wren, Yvonne
Abstract: Background: Children with cleft palate with or without cleft lip (CP±L) are at high risk of problems with early speech sound production, and these difficulties can persist into later childhood. Early intervention could help to reduce the number of children whose problems become persistent. However, much research in the field to date has focused on older children. There is a need to determine if providing intervention during the phase of early typical speech development leads to better outcomes. Aims: To review the evidence for the effectiveness of interventions targeting speech, delivered in the first 3 years of life for children with CP±L, and discuss factors such as intervention type, facilitator, dosage, outcome measures and the age of the child. Methods & Procedures: The systematic review was registered with PROSPERO (CRD42019121964). Eight bibliographic databases including CINAHL and MEDLINE were searched in August 2018. Studies were included if participants received speech and language interventions before 37 months and if they reported outcomes for speech. Two reviewers independently completed inclusion reviews, quality analysis and data extraction. Outcome & Results: The review included seven papers: one pilot randomized controlled trial, one controlled trial, four cohort studies and one case series report. Interventions largely took a naturalistic approach, namely focused stimulation and milieu teaching. The findings provide preliminary support for naturalistic interventions and suggest that these interventions can be delivered by parents with suitable training. Studies included in the review provided low‐strength evidence with variation in both the type of intervention, the manner of delivery and in the risk of bias in the designs used. Conclusions & Implications: The papers included in this review suggest that early naturalistic interventions can have positive impacts on the speech development of children with CP±L. However, the reported methodological quality of the publications overall was weak, and the current evidence lacks clarity and specificity in terms of therapy technique, delivery and optimum age of delivery. Future research should use more robust methodological designs to determine whether early speech interventions are beneficial for children born with CP±L. What this paper adds: What is already known on the subject: Children with CP±L show difficulties with early speech development and often have restricted speech sound inventories. They may reach the canonical babbling stage later than children without CP±L and studies have shown that 20% of children with CP±L have speech which is considered unintelligible or barely intelligible at age 5. It has been proposed that early intervention can lessen the impact of CP±L on speech development. However, currently, the evidence for early interventions for children with CP±L is limited, with the majority of studies focusing on children aged 3 years and older. What this paper adds to existing knowledge: This paper reviews the evidence for different types of early interventions for speech provided to children born with CP±L and whether these interventions are effective in supporting speech sound development. In this review, early intervention is defined as intervention provided to children in the first 3 years of life. This review describes intervention approaches and how they are delivered for this population. What are the potential or actual clinical implications of this work?: In the UK, children born with CP±L and their families are supported by National Health Service (NHS) services over a 20‐year period and speech and language therapy sessions may take place over many weeks and months. If providing early intervention in the first 3 years of life is effective, there is the potential for improved speech outcomes in early childhood and a reduced burden of care on children, families and services. This review considers the evidence for early speech intervention for children with CP±L in the first 3 years of life and identifies areas for future research.